The art of article writing : writing & publishing article using AI for high impact journal - Sahrir, Muhammad Sabri (Tinta Hikmah Consultancy, 2025)
An e-book in WRITING &PUBLISHING ARTICLE USING AI FOR HIGH IMPACT JOURNALS.